Finnish online education cooperation with Asian higher education institutions: recommendations for future projects - Sava Ville (Centre For East Asian Studies, University of Turku, 2025)
The COVID-19 pandemic that hit the world in 2020 forced us to rearrange educational programmes in unexpected ways. This has accelerated new thinking and innovation in education. In order to gauge how Finnish education cooperation projects with Asian partner institutions have met the challenges and identified good practices, a survey was conducted by the Finnish University Network for Asian Studies as part of the Digitree project funded by the Finnish National Agency for Education.
This report summarises management and cooperation practices that have worked well, as well as issues that could be improved upon for the benefit of future projects. Since the sample size was rather small, this report does not claim to have any definitive answers. However, it hopes to provide some perspectives for potential future education cooperation projects and shed light on new forms of online education cooperation that many projects have been driven towards due to the pandemic. Some of the responses to the survey contained generally applicable points that are usable not only with Asian, but other international cooperation partners as well. They could also be applied to both online and offline forms of cooperation.